Roadside Americans : The Rise and Fall of Hitchhiking in a Changing Nation - Reid, Jack (Book collections on Project MUSE., 2020)
"Between the Great Depression and the mid-1970s, hitchhikers were a common sight for motorists, as American service members, students, and adventurers sought out the romance of the road in droves. Beats, hippies, feminists, and civil rights and antiwar activists saw "thumb tripping" as a vehicle for liberation, living out the counterculture's rejection of traditional values. Yet, by the time Ronald Reagan, a former hitchhiker himself, was in the White House, the youthful faces on the road chasing the ghost of Jack Kerouac were largely gone--along with sympathetic portrayals of the practice in state legislatures and the media"--